2011
DOI: 10.1080/17405629.2011.567061
|View full text |Cite
|
Sign up to set email alerts
|

Connecting the intrapersonal to the interpersonal: Autonomy, voice, parents, and romantic relationships in emerging adulthood

Abstract: Multiple forms of adolescent autonomy (emotional autonomy, voice, and cognitive autonomy) were examined as correlates of parental and partner relationships. Measures included parental warmth and psychological control, and romantic support and negative interactions. Participants were 206 students (age 17 to 20, M age ¼ 18) who had romantic partners. Those who reported more emotional autonomy from parents (e.g., individuation and nondependence) reported less voice with parents and less cognitive autonomy. Adoles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…A child with a psychologically controlling parent is therefore expected to refrain from disclosure in order to avoid being exposed to the use of these techniques (Soenens et al., ). This is in line with research showing that parental psychological control serves to undermine adolescents' voice with parents, including their articulation of personal experiences (Zimmer‐Gembeck, Madsen, & Hanisch, ). Whereas some studies have found evidence consistent with a negative relationship between parental psychological control and a child's willingness to share information (e.g., Soenens et al., ; Urry, Nelson, & Padilla‐Walker, ), others have reported no such relationship (e.g., Hunter et al., ).…”
supporting
confidence: 88%
“…A child with a psychologically controlling parent is therefore expected to refrain from disclosure in order to avoid being exposed to the use of these techniques (Soenens et al., ). This is in line with research showing that parental psychological control serves to undermine adolescents' voice with parents, including their articulation of personal experiences (Zimmer‐Gembeck, Madsen, & Hanisch, ). Whereas some studies have found evidence consistent with a negative relationship between parental psychological control and a child's willingness to share information (e.g., Soenens et al., ; Urry, Nelson, & Padilla‐Walker, ), others have reported no such relationship (e.g., Hunter et al., ).…”
supporting
confidence: 88%
“…Our participants expressed a desire to move away from their parents by establishing a separate residence. This interpersonal shift has been linked to intrapersonal development related to individuation (Zimmer-Gembeck, Madsen, & Hanisch, 2011). At the same time, participants felt close to family, enjoyed many benefits while living at home, and worried about how their parents would cope when they left.…”
Section: Discussionmentioning
confidence: 99%
“…However, other authors dispute the argument that achieving emotional autonomy is a developmental task, supporting instead the theory that adolescents who feel more emotionally autonomous from their parents perceive lower quality, less affection and less love in their relationships with them (Ryan & Lynch, ; Zimmer‐Gembeck, Madsen & Hanisch, ). These studies have also shown that high levels of emotional autonomy are associated with challenges in family relationships during adolescence and emerging adulthood, less cohesive family structures marked by a lack of emotional intimacy and communication, and more difficult parent‐child relationships (Neff & Harter, ; Yu, ).…”
Section: Introductionmentioning
confidence: 99%